Strength through adversity: Moderate lifetime stress exposure is associated with psychological resilience in breast cancer survivors - Dooley, Larissa N. (Stress Health, 2017)
Stress research typically emphasizes the toxic effects of stress, but recent evidence has suggested that stress exposure, in moderation, can facilitate resilience. To test whether moderate stress exposure promotes psychological resilience to cancer, we examined the relationship between lifetime stress exposure prior to cancer diagnosis and postdiagnosis psychological functioning among 122 breast cancer survivors. Lifetime acute and chronic stress was assessed using an interview-based measure, and psychological functioning was assessed using measures of cancer-related intrusive thoughts and positive and negative affect. Results indicated that acute stress exposure was associated with cancer-related intrusive thoughts in a quadratic fashion (p = .016), such that participants with moderate acute stress reported fewer intrusive thoughts compared to those with low or high acute stress. Similarly, a quadratic relationship emerged between acute stress exposure and positive affect (p = .009), such that individuals with moderate acute stress reported the highest levels of positive affect. In contrast, acute and chronic stress were related to negative affect in a positive, linear fashion (ps < .05). In conclusion, moderate stress exposure was associated with indicators of psychological resilience among breast cancer survivors, supporting stress exposure as a key factor influencing adjustment to breast cancer and providing evidence for stress-induced resilience in a novel population.